ANDROID-BASED KEKASIH EDUCATIONAL STRATEGY TO IMPROVE PREGNANT WOMEN’S LITERACY ON EXCLUSIVE BREASTFEEDING - Epti Yorita; Rina; Mariati (Poltekkes Kemenkes Banten, 2026)
Despite existing health policies and breastfeeding support programmes, the coverage of exclusive breastfeeding in several areas of Bengkulu City remains low. Contributing factors include pre-lactation feeding, cultural influences, limited knowledge and inadequate access to reliable information. Therefore, a health education strategy that provides continuous access to information for pregnant women is needed to improve literacy about exclusive breastfeeding during pregnancy, using the Android-based KEKASIH digital education programme. This quasi-experimental study involved 70 women in their third trimester of pregnancy, who were divided into two groups: an intervention group, who received exclusive breastfeeding education through the KEKASIH Android application; and a control group, who received conventional antenatal education. Exclusive breastfeeding literacy was measured before and after the intervention using a structured questionnaire. The results showed a significant increase in literacy in both groups. However, the intervention group demonstrated a greater average increase (mean difference: 4.49; p = 0.00) than the control group (mean difference: 3.91; p = 0.00). While there was no significant difference in effectiveness between the two methods based on the Mann-Whitney test (p = 0.15), digital education demonstrated a greater improvement in breastfeeding literacy. These findings suggest that the KEKASIH Android application can be used as an effective strategy for improving breastfeeding literacy among pregnant women.